(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Social Communication Emotional Regulation Transactional Support (SCERTS) model is based on studies and has manuals for assessing children and designing individual treatment plans. However, limited research has been done to evaluate the efficacy of this model. This study attempts to evaluate the impact of SCERTS model-based intervention on children with Autism Spectrum Disorder (ASD) in Lahore with the objective to determine the usefulness of SCERTS in promoting language development and improvement in social skills in children with ASD. Patients and methods: This quasi experimental study was conducted at Roots and Wings autism center, located in Bahria Town Lahore, for the duration of nine months. Children with formal diagnosis of Autism Spectrum Disorder, with age range of 3 years to 6 years old. Prior to intervention and subsequently after that, the children were evaluated with the portage checklist in the domain of language and socialization skills. Results: Participating children demonstrated improvement in their language and social skills after the intervention, as assessed by portage. Conclusion: SCERTS based intervention can facilitate children with autism spectrum disorder to improve their language and social communication skills.